PEMANFAATAN CITRA HYPERION UNTUK GRANULOMETRI SEDIMEN DI MUARA KALI BRANTAS - , RHEZA ARIFN ZEIN, Drs. Sudaryatno, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Brantas River estuary has a sediment grain size varies. Each difference in sediment has different characteristic of spectral reflectance. Hyperion Image which is hyperspectral imagery expected to be able to distinguish the types of sediments that exist at Brantas River estuary. According to hyperspectral images ability have a lot of bands in the spectral range of narrow electromagnetic waves. The purpose of this study was (1) to determine the characteristics of spectral reflectance curves granulometry sediment types of Hyperion imagery in Brantas River estuary, (2) to determine the distribution of classification granulometri sediments in Brantas River estuary (SAM classification method and classification accuracy assessment), and (3) to determine Hyperion imagery ability for comparating granulometry sediment variation. The research method is used in this study have three stages. First stage is data preparation, including atmospheric and geometric correction. Second stage is processing data, including classifiying sediments according to Unsupervised Iterative Self-Organizing Data Analysis Technique (ISODATA) classification, the determination of pure pixels was performed using Minimum Noise Fraction (MNF) and Pixel Purity Index (PPI), determining Endmember and sampling sediment texture, and executing Spectral Angle Mapper (SAM) classification. Third stage is Analysis. Results of this study show that Hyperion imagery can be used to distinguish granulometry sediment. Characteristic of spectral reflectance curve for granulometry sediment indicate that greater grain size has higher intensity of the spectral reflectance. Sediment grain size by grade sand (0.125 to 0.250 mm) is located on the river embankments. Whereas grain size by grade clay and silt (0.0003 to 0.063 mm) are located on the dynamics of coastal areas. Accuracy of SAM classification (threshold 0.36) is 54.55% and index kappa is 0.49.Granulometry sediment is effective when the sample exist in a land surface.